Correlation between IL-6 and Age in COVID-19: Insights from a Cross-Sectional Analysis in Malang, Indonesia - Agustin Iskandar; Dearikha Karina Mayashinta; Catur Suci Sutrisnani; Nur Samsu; Agustina Tri Endharti; Edy Widjajanto (مجلة بغداد للعلوم)
Interleukin 6 (IL-6) has been identified as a predictor of severity and mortality in COVID-19. Although morbidity and mortality generally increase with age, it remains uncertain whether there is a correlation between age and IL-6 levels, thereby exacerbating the severity of COVID-19 in patients. The objective of this study was to examine the correlation between age and IL-6 levels in COVID-19 patients. The study was  cross-sectional, analyzing laboratory and medical records of 3,171 COVID-19 patients who received treatment in 2021 at Saiful Anwar General Hospital. The Data analyzed using Kruskal-Wallis, Dunnett's Post Hoc, and Spearman Correlation tests. The patients were divided into four age groups: <20 years (1.29%), 20-40 years (18.10%), 40-60 years (43.74%), and >60 years (36.87%). The respective mean levels of IL-6 in each group were 39.44, 192.04, 217.27, and 252.59 pg/ml. A significant difference (p-value = 0.000) was observed in IL-6 levels between the <20 years age group and the other groups. Moreover, a significant positive correlation (p-value = 0.000) was identified between age group and IL-6 levels in COVID-19 patients, indicating higher IL-6 levels in older patients. In conclusion, there were differences in IL-6 levels based on age groups and age was positively correlated with IL-6 levels in COVID-19 patients.